Cultural heritage and sustainability as an essential disposition for music graduates - Reid, A.; Bennett, Dawn; Peres da Costa, N.; Petocz, P. (HERDSA, 2013)
Music is one of the cultural industries, part of a group of intangible cultural assets whose sustainability is included in the fourth ‘pillar of sustainability’. For students of music, cultural heritage and sustainability form an important component of professional preparation. However, this graduate disposition is not much researched nor well understood. While there is some recent research describing the use of music for cultural sustainability in contemporary Indigenous contexts, there is very little that describes the importance of music for culture in urbanised communities. The idea of ‘creolisation’ – the development of a new culture from combination of traditional ones – is a useful concept for broadening the understanding of music for cultural sustainability. More practically, cultural heritage and sustainability can be explored pedagogically by looking at musical artefacts and performance practices from different cultures and times, and investigating their translation into contemporary professional music practice. Understanding the role of cultural heritage and sustainability as a graduate disposition will enable a productive pedagogical interplay between music pedagogy and students’ contribution to society in their working life.